Vertical distribution of Aedes mosquitoes in multiple storey buildings in Selangor and Kuala Lumpur, Malaysia - Lau, K.W.; Chen, Chee Dhang; Lee, H.L.; Izzul, A.A.; Asri-Isa, M.; Zulfadli, M.; Sofian-Azirun, Mohd (Malaysian Society of Parasitology and Tropical Medicine, 2013)
The aim of the present study was to determine the vertical distribution and abundance of Aedes mosquitoes in multiple storey buildings in Selangor and Kuala Lumpur, Malaysia. Ovitrap surveillance was conducted for 4 continuous weeks in multiple storey buildings in 4 residential areas located in Selangor Kg. Baiduri (KB) and Kuala Lumpur Student Hostel of University of Malaya (UM), Kg. Kerinchi (KK) and Hang Tuah (HT). The results implied that Aedes mosquitoes could be found from ground floor to highest floor of multiple storey buildings and data from different elevation did not show significant difference. Ovitrap index for UM, KB, HT and KK ranged from 0 - 29.17%, 0 - 55.56%, 8.33 - 83.33% and 0 - 91.17% respectively. Aedes aegypti and Aedes albopictus were found breeding in HT, KK and KB; while only Ae. albopictus was obtained from UM. The results indicate that the invasion of Aedes mosquitoes in high-rise apartments could facilitate the transmission of dengue virus and new approaches to vector control in this type of residential area should be developed.